2011
DOI: 10.5114/wiitm.2011.26256
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral index and cerebral oximetry in low-flow and high-flow rate anaesthesia during laparoscopic cholecystectomy - a randomized controlled trial.

Abstract: IntroductionThe need to reduce pollution emissions in the operating room and to reduce treatment costs motivates more frequent use of general anaesthesia with a small or minimal fresh gas flow rate. Nevertheless, the reduction of the delivery of fresh gases should not influence the quality and safety of the anaesthesia.Material and methodsA total of 105 elective laparoscopic cholecystectomy patients were included in the study. There were 72 female (68.6%) and 33 male (31.4%) patients. Patients were randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
3
6
1
Order By: Relevance
“…We did not observe any significant changes in the tissue oxygen saturation while increase in the IAP. This observation is in a good agreement with reports of other authors [23][24][25][26][27][28][29][30][31] where only small changes (increase or decrease) in the saturation were noted. In 3 out of 8 studies no significant changes in StO2 were reported.…”
Section: Discussionsupporting
confidence: 93%
“…We did not observe any significant changes in the tissue oxygen saturation while increase in the IAP. This observation is in a good agreement with reports of other authors [23][24][25][26][27][28][29][30][31] where only small changes (increase or decrease) in the saturation were noted. In 3 out of 8 studies no significant changes in StO2 were reported.…”
Section: Discussionsupporting
confidence: 93%
“…We did not observe significant differences between low-flow and normal-flow groups with respect to HR and SpO 2 . Similarly, Kupisiak et al reported no significant differences between patients who received low-flow and high-flow anesthesia during laparoscopic cholecystectomy with respect to HR, MAP, EtCO 2 , and SpO 2 ; patients also did not have a high risk of awakening from anesthesia [9]. Although we found that the MAPs of the low-flow group were significantly higher than the normal-flow group at T 2 , T 3 , and T 4 , the higher MAPs were considered clinically negligible because the MAPs did not increase by 20% above baseline during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, BIS is the most effective method for assessing depth of anesthesia and sedation. BIS monitoring reduces the number of intraoperative wake-ups in patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…A few groups have studied the effects of low-flow anesthesia on hemodynamic and pulmonary functions and in these studies isoflurane and desflurane were used as volatile anesthetic agents [ 18 , 23 ]. Bilgi et al [ 1 ] compared FVC and FEV1 levels after low-flow and high-flow anesthesia with desflurane as the inhalation anesthetic agent and observed a decrease in FVC and FEV1 levels in both groups on the postoperative first day, but, in the low-flow anesthesia group, the decrease was much greater than in the high-flow anesthesia group.…”
Section: Discussionmentioning
confidence: 99%